2016
DOI: 10.1515/hc-2015-0234
|View full text |Cite
|
Sign up to set email alerts
|

Three-component synthesis of new o-hydroxyphenyl-substituted pyrazolo[3,4-b]pyridines promoted by FeCl3

Abstract: An efficient three-component synthesis of o-hydroxyphenyl-substituted pyrazolo[3,4-b]pyridines from substituted salicylic aldehydes, β-keto esters and 5-aminopyrazoles in the presence of FeCl3 is presented. Newly synthesized compounds were fully characterized by means of 1H NMR, 13C NMR, IR, HRMS and elemental analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Fan et al demonstrated the FeCl 3 -catalyzed three-component one-pot synthesis of pyrazolo [3,4-b]pyridines 557 in good yields by reacting ethyl 4,4,4-trifluoro-3-oxobutanoate 1 with substituted salicylic aldehydes 489 and 5-amino-3-methyl-1phenylpyrazole 516 (Scheme 196). [300] Modest reaction conditions and wide substrate scope were some of the advantages of this protocol.…”
Section: Other Fused and Bridgehead Heterocyclesmentioning
confidence: 99%
“…Fan et al demonstrated the FeCl 3 -catalyzed three-component one-pot synthesis of pyrazolo [3,4-b]pyridines 557 in good yields by reacting ethyl 4,4,4-trifluoro-3-oxobutanoate 1 with substituted salicylic aldehydes 489 and 5-amino-3-methyl-1phenylpyrazole 516 (Scheme 196). [300] Modest reaction conditions and wide substrate scope were some of the advantages of this protocol.…”
Section: Other Fused and Bridgehead Heterocyclesmentioning
confidence: 99%
“…Recently the reaction of β-ketoesters 81 as in the three-component reaction with 5-aminopyrazoles 16 and substituted salicylic aldehydes 83 was also studied by Fan et al [ 69 ] . An extensive survey of catalysts and solvents identified 0.2 equivalents of FeCl 3 and ethanol as optimal catalyst and solvent, respectively, with which o -hydroxyphenylpyrazolo[3,4- b ]pyridine derivatives 85 were obtained in 89% yields with no formation of the cyclized isomer chromenopyrazolo[3,4- b ]pyridine 86 .…”
Section: Reviewmentioning
confidence: 99%
“…When 5-amino-3-methyl-1-phenylpyrazole ( 21 ) reacted with aldehydes 1 and other CH-acids (acetoacetic acid derivatives), e.g., 98e,f (Fan et al, 2016 ), 3-oxo-3-phenylpropanenitrile 107 (Huang et al, 2011 ; Rahmati and Khalesi, 2012 ) heteroaromatic pyrazolopyridines 128 (similar to compounds 126 ) and 129 (similar to compounds 118a , Figure 8 ) were formed (Figure 10 ).…”
Section: Main Partmentioning
confidence: 99%